PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSI DAN KECERDASAN SPIRITUAL TERHADAP KINERJA PEGAWAI KANTOR KESYAHBANDARAN UTAMA BELAWAN - Miduk Manalu (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
The Formulation of this research is how the influence of intellectual intelligence, emotional intelligence and spiritual intelligence to the performance of office employees of the main Kesyahbandaran Belawan, and the purpose of this research is to Know and analyze the influence of intellectual intelligence, emotional intelligence and spiritual intelligence to the performance of the Office employees of the main Kesyahbandaran Belawan.This research is a quantitative descriptive study. Data collection techniques are conducted through interviews,questionnairequestions and documentation studies. The samples in this study were as many as 60 employees. Variables are measured at Likert scale. Hypothesis testing using multiple linear regression analyses through F-test and T-Test. The Results of the test in Unison showed that intellectual intelligence, emotional intelligence and spiritual dextancy have significant effect on employee performance variables at the Kesyahbandaran office Belawan with a coefficient of determination value of 0.552 or 55.2%. Partially, intellectual intelligence is positive and significant to the employee's performance at the main Belawan's office of Kesyahbandaran with a regression coefficient value of 0456 or 45.6%. Emotional Intelligence has a positive and significant effect on employee performance at the Belawan main Kesyahbandaran office with a regression coefficient value of 0251 or 25.1%. Spiritual Intelligence is positive and significant to the employee's performance at the Belawan main Kesyahbandaran office with a regression coefficient value of 0274 or 27.4%. The highest value of a regression coefficient is intellectual intelligence of 45.6%.